Pengaruh Return On Asset, Debt To Equity Ratio, Dan Current Ratio Terhadap Nilai Perusahaan Sektor Industri Tambang di Bursa Efek Indonesia Periode 2016-2019 - Muhamad Solihin; Sofyan Halim (Universitas Mercu Buana, 2022)
This study is to determine the effect of Return On Asset (ROA), Debt To Equity Ratio (DER), and Current Ratio (CR) on Firm Value. The object of this research is the mining sector which is listed on the Indonesia Stock Exchange in 2016-2019. This research was conducted on 72 samples using a quantitative descriptive approach. Therefore, the data analysis used is statistical analysis in the form of multiple linear regression tests. The results of this study indicate that partially, the variable Return On Asset (ROA), Current Ratio (CR) and Debt to Equity Ratio (DER) have a significant effect on the value of the mining sector companies listed on the Indonesia Stock Exchange. This is evidenced by the results of the partial test (Tongan test) which also shows the significant value of the three independent variables that support the hypothesis. The simultaneous test results (F test) also show that the independent variable simultaneously affects the dependent variable. Therefore, the results of this study found that there is a significant influence between Return on Assets (ROA), Current Ratio (CR) and Debt To Equity Ratio (DER) on Company Value listed on the Indonesia Stock Exchange